Hubungan Pengetahuan Dan Sikap Ibu Dengan Pemberian Makanan Pendamping Asi (MP -ASI) Pada Anak Usia 6 - 24 Bulan Di Puskesmas Bandar Kabupaten Bener Meriah Tahun 2022 - Lesri Tampubolon; Retno Wahyuni; Edy Marjuang; Basaria Manurung (Jurnal Anestesi, 2023)
The time to give MP-ASI to babies is after the baby is 6 months old because before the age of 6 months the baby's digestion is not yet strong enough to digest food other than breast milk. However, there is still a lack of babies who receive Complementary Food (MP-ASI) before the time of giving it which cannot be separated from the influence of knowledge and attitudes of parents, in this case mothers who are less aware and have complete information regarding the correct provision of MP-ASI but instead give MP-ASI breastfeed before the baby is 6 months old. To find out the relationship between maternal knowledge and attitudes and providing MP-ASI to children aged 6 - 24 months at the Bandar Health Center, Bener Meriah Regency in 2022. This type of research is analytical observational research using a cross sectional approach. Sampling in this study was carried out with a total sampling of 48 mothers who had children aged 6 - 24 months. Based on statistical tests carried out with Chi-Square, it shows that the p value = 0.023 < 0.05, then Ho is rejected and Ha is accepted which can be interpreted as meaning that there is a relationship between maternal knowledge and providing MP-ASI to children aged 6 - 24 months at the Community Health Center. Bener Meriah Regency City in 2022.